Surface phosphorization of Ni–Co–S as an efficient bifunctional electrocatalyst for full water splitting. Issue 45 (5th November 2021) - Yang, Hua; Lin, Kangdi; Zhou, Zihao; Peng, Chenting; Peng, Shaomin; Sun, Ming; Yu, Lin
Abstract : The surface phosphorization of NiCo2 S4  make it exhibit superior electrochemical activity, which is ascribed to the modulation of electronic structure, the rise of conductivity, the promotion of electrochemical surface area and the active sites. Abstract : Exploring efficient bifunctional electrocatalysts is of great importance for water splitting to obtain scalable and sustainable hydrogen generation. The strategy of element modification is effective for tuning the electronic structures of electrocatalysts. Herein, binder-free, phosphorus-doped NiCo2 S4 /CFP (Ni–Co–S–P) was synthesized under hydrothermal conditions, followed by surface phosphorization via solid reaction. The incorporation of P modulates the electronic structure of the Ni–Co–S–P catalyst, increases the electrical conductivity, and promotes the electrochemical surface area and the number of active sites, thereby improving its activity. The Ni–Co–S–P catalyst delivers a current density of 10 mA cm −2 at an overpotential of 176 mV for the hydrogen evolution reaction (HER) and an overpotential of 265 mV for the oxygen evolution reaction (OER). When assembled into an electrolyzer both as a cathode and anode, it demonstrated outstanding activity for overall water splitting to afford a potential of 1.76 V at 10 mA cm −2 with no obvious decay after 25 h.